Draft Genome and Plasmid Sequences of Chlamydia pneumoniae Strain B21 from an Australian Endangered Marsupial, the Western Barred Bandicoot - Roulis, Eileen (American Society for Microbiology, 2014)
Chlamydia pneumoniae is a ubiquitous intracellular pathogen, first associated with human respiratory disease and subsequently detected in a range of mammals, amphibians, and reptiles. Here we report the draft genome sequence for strain B21 of C. pneumoniae, isolated from the endangered Australian marsupial the western barred bandicoot.